Indonesia Transport Loan Projects: Development Outcome Attributions (DOA) on Unemployment, Growth, and Poverty - Ingratubun, Muhammad A; Fauzi, Akhmad; Siregar, Hermanto; Nuryartono, R Nunung (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2024)
Our goal was to investigate the effects of international development banks' foreign exchange loan-funded transportation projects. We examined the effects and efficacy of Indonesia's transport loan projects, which were supported by the World Bank and the Asian Development Bank (ADB), to achieve this, 67 projects of $8.85 billion in value were undertaken between 1972 and 2020. This study is significant because it is the first in the history of development assistance—after 100 years—that is based entirely on banking theories and practices, employing attribution techniques and presuming that all loans will be disbursed into Indonesia's economy. Nevertheless, the effectiveness narratives are untrue because—after being converted into Rupiah—less than 10% of the loan fund made it to Indonesia's economy. According to our analysis, the loans from both banks decreased growth by 200% and increased poverty by 220%, even if they were successful in providing jobs. The disbursement delays of five to seven years result in capital outflows of more than $26 for every $1 loan. Fixing this necessitates a 100% payout in Rupiah into Indonesia's national banking systems the same year that the loan agreements are executed.